Factors associated with grazing behavior in candidates for bariatric surgery at a hospital in the Amazon - Kikuchi, Jeane Lorena Dias; Carvalhal, Manuela Maria de Lima; de Castro, Mariana Maués; Vieira Lourenço-Costa, Vanessa; dos Santos, Carlos Armando Ribeiro; Cunha, Flávia Siqueira; Paracampo, Carla Cristina Paiva; Gomes, Daniela Lopes (Frontiers in Public Health, 2023)
To assess grazing behavior and associated factors in candidates for bariatric surgery monitored at a public hospital that is a reference in the care of people with severe obesity. Cross-sectional analytical study, with candidates for bariatric surgery of both genders, treated in a public hospital in the Amazon. To assess grazing behavior, the Repetitive Eating Questionnaire was used, and to investigate patterns of eating behavior, the Three Factor Eating Questionnaire was used, which assesses: Emotional Eating, Cognitive Restriction and Uncontrolled Eating. Sociodemographic information was obtained through self-report and the description of medication use through the medical record. Body mass index (BMI) was also calculated by measuring weight and height. The SPSS program, v. 21.0 was used. The study was approved by the Research Ethics Committee. A total of 205 participants were evaluated, with a mean age of 37.5 ± 8.6 years, the majority (93.7%) being women and the majority (59.5%) was not also using medication to lose weight. About 66.3% of the participants had compulsive grazing. The factor with the highest score was cognitive restriction (p<0.001). Individuals who used weight loss drugs had higher scores in the cognitive restriction factor (p=0.015) and lower scores for uncontrolled eating (p= 0.008), compulsive grazing (p=0.021) and non-compulsive grazing (p=0.034). Linear regression showed that emotional eating and uncontrolled eating were predictors of both compulsive grazing and non-compulsive grazing behavior. It was observed that grazing behavior, cognitive restriction, emotional eating and uncontrolled eating are present and correlated in the studied patients. In addition, the use of weight loss drugs seems to help reduce dysfunctional eating behaviors in patients with severe obesity.